Strengthening Basic Literacy Through Memorization of The Qur'an: Studies on Migrant Children in Non-Formal Education - Wijayanti, Berly; Ishari, Nurhafid (Fakultas Agama Islam Universitas Billfath, 2025)
This study describes and analyzes the strengthening of basic literacy and memorization of the Qur'an for migrant children at the Malaysian Center for Non-Formal Education Teaching and Learning Activities to fulfill non-formal education rights and develop religious values. A qualitative approach with an ethnographic design was used, where the researcher was directly involved in the learning process to understand the students' patterns of interaction, experiences, and social dynamics. Data were collected through participatory observation, semi-structured interviews with students, teachers, and the principal, and documentation of learning activities. These data were then analyzed inductively through data reduction and presentation. The study results showed increased basic literacy skills, including recognizing Latin and Hijaiyah letters, reading, and memorization skills, particularly of Surah Al-'Ashr, using the talaqqi and takrir methods. Reading activities in the context of Islamic education have deep spiritual meaning because they are in harmony. The novelty of this research lies in integrating literacy and memorization into the non-formal education of migrant children, a topic that has not been widely studied. The findings confirm the critical role of the Malaysian Center for Non-Formal Education Teaching and Learning Activities as an alternative institution that supports academic development while shaping students' character and Islamic identity, especially for children who do not receive formal education abroad. In practical terms, the results of this study can guide non-formal educators in designing compelling reading and memorization programs, enabling migrant children to develop their academic abilities and spiritual values optimally.